Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the inverse of the function [tex]\( y = 2x^2 - 4 \)[/tex], we need to follow several steps.
1. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
The given equation is:
[tex]\[ y = 2x^2 - 4 \][/tex]
To find the inverse, we swap [tex]\( y \)[/tex] and [tex]\( x \)[/tex]:
[tex]\[ x = 2y^2 - 4 \][/tex]
2. Solve for [tex]\( y \)[/tex]:
Now, we need to isolate [tex]\( y \)[/tex]:
- First, add 4 to both sides:
[tex]\[ x + 4 = 2y^2 \][/tex]
- Next, divide both sides by 2:
[tex]\[ \frac{x + 4}{2} = y^2 \][/tex]
- Finally, take the square root of both sides. Remember to consider both the positive and negative roots:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
3. Write the inverse function:
The inverse function can be expressed as:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
Therefore, the inverse of the function [tex]\( y = 2x^2 - 4 \)[/tex] is:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
From the given choices, this corresponds to:
[tex]\[ y = \pm \sqrt{\frac{x+4}{2}} \][/tex]
1. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
The given equation is:
[tex]\[ y = 2x^2 - 4 \][/tex]
To find the inverse, we swap [tex]\( y \)[/tex] and [tex]\( x \)[/tex]:
[tex]\[ x = 2y^2 - 4 \][/tex]
2. Solve for [tex]\( y \)[/tex]:
Now, we need to isolate [tex]\( y \)[/tex]:
- First, add 4 to both sides:
[tex]\[ x + 4 = 2y^2 \][/tex]
- Next, divide both sides by 2:
[tex]\[ \frac{x + 4}{2} = y^2 \][/tex]
- Finally, take the square root of both sides. Remember to consider both the positive and negative roots:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
3. Write the inverse function:
The inverse function can be expressed as:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
Therefore, the inverse of the function [tex]\( y = 2x^2 - 4 \)[/tex] is:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
From the given choices, this corresponds to:
[tex]\[ y = \pm \sqrt{\frac{x+4}{2}} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.